2014
DOI: 10.1080/15426432.2014.873294
|View full text |Cite
|
Sign up to set email alerts
|

Santería as Informal Mental Health Support Among U.S. Latinos with Cancer

Abstract: This article explores and examines Santería’s function as a culturally congruent informal mental health support that assists U.S. Latinos to cope with the psychosocial sequelae of living with cancer. Research has demonstrated that Santería serves as a mediating institution for many Latinos. The tradition functions as both a religion and a health care system within various Latino subgroups and has functioned as an informal mental health service in occurrences of health versus illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Resulting emotional problems can be exacerbated by lack of support, information, and skills to manage illness [44, 45]. Also, men with cancer are less likely than women to use health and psychological support care services [4650] and have significant unmet psychosocial and health system/information needs [51, 52].…”
Section: Introductionmentioning
confidence: 99%
“…Resulting emotional problems can be exacerbated by lack of support, information, and skills to manage illness [44, 45]. Also, men with cancer are less likely than women to use health and psychological support care services [4650] and have significant unmet psychosocial and health system/information needs [51, 52].…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 15 , 25 , 40 , 41 Santerias are commonly used by THs and function as the visible door to the invisible world of folk healing. 42 Yerberos use botánicas as a resource for people who seek ethnomedicine and ethnobotany alternative medicine, which contains naturopathic treatments involving herbal teas and foods. 29 , 43 For example people with diabetes use a concoction of herbs as a supplement in addition to their medication 14 , 32 , 37 …”
Section: Resultsmentioning
confidence: 99%
“…Based on the results obtained from semi-structured interviews with 31 religious leaders, community leaders, traditional healers, and biomedical health providers, 10 focus group discussions, and four in-depth case studies of psychiatric patients, the authors concluded that the widespread belief in Vodou was, in and of itself, not a primary barrier for most Haitians to seek biomedical care but that its interventions were not always considered effective for the treatment of mental disorders, while many could not afford such help ( Khoury et al., 2012 ). This is strikingly at odds with Rosario and de la Rosa (2013) who, analysing the extant literature on the use of Santería practices by Latino cancer patients in the US, concluded that those in need of mental health services in addition to their cancer treatment often took recourse to Santería rather than to Western biomedical care services. Principal reasons they outlined for this included the perceived incompatibility of Latino and Western illness and treatment needs, and the insufficiency of Western mental health services to adequately incorporate foundational cultural values.…”
Section: Discussionmentioning
confidence: 95%